A simulation model for wave propagation and scattering of beam waves in vegetation using scalar transport theory. (2nd January 2017) - Wu, Michael Y.-C.; Lin, Jian (Denny); Sun, Nanfei
Abstract: Representing an accurate model of how pulse waves are propagated and scattered in the vegetation is an interest in the area of wireless communications. Several research projects on this problem have supplied similar techniques using scalar transport theory when the incident, pulse waves have been altered to emulate a particular radiation condition in the real world. This paper will principally investigate a simulation model – a digital prototype that represents a physical problem – to correlate among these research projects that have tendencies of evolving progressively by facilitating a model-driven approach, thus establishing some of the computational models reliably. By providing summaries of these research projects, this paper has identified all commonalities and differences among these projects to delineate them into a simulation model, which is then divided into smaller submodels. These submodels are further validated to meet the minimum error criteria and conditions for better numerical results. Consequently, these models will permit effortless enhancements when new computational resources and theories have become available.